Summary: Democratic Institutions and Long Term Action: Exploring the Institutional Antecedents of Presentism and Intergenerational Justice - Vermassen, Daan Peter (Politics of the Low Countries, 2025)
The political decisions we make (or do not make) today affect not only the current generation of voters but also generations of the future as intertemporal policy dilemmas require us to distribute costs and benefits over time (Jacobs, 2011). This is especially apparent in the many long-term policy challenges we face, such as climate change, public debt and pension policies. Yet our current, representative democracies are notorious for their bias towards the present (MacKenzie, 2021). Several institutional dynamics continuously draw the attention of representative democracies to the present and incentivise politicians to focus on securing current-day benefits, while refraining from making policy investments (Boston, 2017; MacKenzie, 2021; Smith 2021).